Curadoria de si: estratégias de criação e de pertencimento na arte contemporânea - Letícia Weiduschadt (2021)
The thesis investigates the creative strategies of artists Marco Paulo Rolla, Nelson Leirner and Tatiana Blass. Between the emission of the artist's voice, the understanding of the creative process and his ways of doing, he discusses choices aimed at his insertion in the art market. In the first part of the thesis, entitled “Perennial Routes, Impossible Encounters” we investigate, through a historical perspective, the artists’ writings and the use of interviews as a reference source for reflection on the processes of creation. From this, we will also present the methodology based on the ANT proposal, systematized by Bruno Latour. Next, we will advance on our proposal to think about the contemporary creative process as a convolution in relation to two central axes: the artist's intention and his experience. In “About the distance between me and you”, title attributed to the second part of the thesis, the conceptual construction of the artist's work is discussed, inferring an analysis that crosses the philosophy and history of art. Still in this part, reflecting on the creation of the artist's image and based on the interviews conducted with the three main artists in the research and some agents who relate to them in some works of art, we will build a reading on their creation strategies in relation the polarity between manual making and the outsourcing of artistic making. In the third part of the thesis, we will investigate how the art system interferes in the construction of sense of belonging in place of the economic success of the arts. Finally, defending the comprehension that the contemporary artist is atypological.